STATISTICAL QUALITY CONTROL (SQC) PADA PROSES PRODUKSI PRODUK âEâ DI PT DYN, TBK - Handes, Dicky; Susanto, Kishi; Novita, Lusia; Wajong, Andre M. R. (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
This study discussed about the quality control of product E produced by PT DYN, Tbk., a plasticÂ packaging manufacturer in Jatake, Banten. P map was used to map whether the product has been in the controlÂ limits or not. Pareto diagram was used in determining the biggest types of defects that occured in the productÂ mapped. Causal diagram was used in determining the cause of defects in the product. For the purposes of theÂ study, we collected data about the amount of production and the amount of defects of product E for threeÂ months as much as 45992. Based on the p map, there were seven data outside the control limits which were 9,Â 27, 30, 42, 43, 48 and 63. There were three biggest flaws obtained from Pareto diagram, i.e. black spots, roughÂ body, and bram. The data was then analyzed using causal diagram. The results showed that the causes of theÂ defects were: (1) human â less conscientious and less skilled ; (2) material â dirty raw materials, (3) methods âÂ the work process did not follow the work standards, (4) machine â inappropriate settings, and (5) environment âÂ dirty. Therefore, the company must make improvements to machinery, materials, methods, human and theÂ environment to reduce products defects.